Business Strategy Formulation for Trans Metro Pekanbaru Using Business Model Canvas and Strategic Environment Analysis - Shifa Dhiah Savitri; Mohammad Riza Sutjipto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to formulate sustainable and competitive business strategies for Trans Metro Pekanbaru (TMP), a public transportation system managed by UPTD under the regional government. Using the Business Model Canvas (BMC) as the primary framework, supported by SWOT, Porter’s Five Forces, and PESTLE analyses, this research identifies the internal and external factors influencing TMP’s performance. The study found major challenges such as decreased ridership, lack of digital integration, and growing dependence on private vehicles. However, the flexibility offered through BLUD-based governance provides opportunities to improve innovation and service performance. Strategic recommendations include enhancing the value proposition, diversifying customer segments, and digitalizing distribution channels. These strategies are expected to strengthen TMP’s competitive advantage and support the development of an inclusive and efficient urban mass transportation system in Indonesia.